A Cultural History of Learning Difficulties in the Modern Age - Barden, Owen (My University, 2020)
My thesis in this chapter is threefold. Firstly, I contend that “learning difficulties” as we now understand them are phenomena created by certain contingent discursive formations. That is to say, they are not natural, but manufactured, and dependent on particular, peculiar historical conditions. Secondly, I contend that “learning difficulties” is an organizing concept: one that has, over the course of the twentieth and twenty-first centuries, irrespective of the shifting signifying terminology used over this period, radically transformed our sense not only of education and learning, but also of who is or is not deemed entitled to full citizenship and its associated rights, and so who is or is not fully human. Thirdly, I contend that a regime of truth has been constructed around “learning difficulties” that privileges certain knowledges and excludes alternative ways of knowing, most notably those of people labeled with learning difficulties. In writing a cultural history, the emphasis is not on what certain people are or are not learning, nor on what anyone’s particular difficulties with learning are perceived to be. Rather, the emphasis is on the role “learning difficulties” play in society. McDermott et al. (2006) put it in the following way in an article elucidating the political work so-called learning difficulties now have to do in Westernized societies:
A Cultural History of Disability in the Modern Age.
Keywords: Inclusive Society; Disability Inclusion; INTELLECTUAL DISABILITIES; LEARNING DISABILITY; Intellectual Disability; Attitudes; Culture; Social exclusion